Diretrizes e perspectivas para o ensino superior de guitarra elétrica no Brasil - Mariano, Anderson de Sousa (2018)
The present research takes a clear look at University level teaching of courses in electric guitar in Brazil, observing the existance of a movement of consolidation in the Brazilian School of electric guitar in it’s multiple musical languages that is verified in Brazilians guitar players style. This movement integrate in itself, based on, the rythmic and harmonic influences of popular genres of Brazilian music, with an expression of universal character which appears in relationship crossing over with a variety of styles including Jazz, Blues, Rock, Classical and Pop, among others commonly encountered. Within this context (prism) we base our research, recognizing some guidelines for the process of teaching and learning of the instrument, educational perspectives that are aligned with the many demands in this field of work and, within a realistic University level education, keeping in mind what the guitar students will encounter and offering parralled autonomy in the traditional processes which refer to academic teachings. To conclude our proposal we bring an integrative perspective of savvy and knowledges studies, including those which will be presented in twelve (12) topics , where even beyond will be integrated between themselves in the study sessions and academic practices are preferentially placed in the context of simulated practices for creative development of the abilities necessary in the formation of a guitarist, signalizing a holistic approach to the study and playing of the instrument, seeking to include the many diverse musical dimensions like a whole thing in musical performances.